Acquisition of Multidrug-Resistant Human Immunodeficiency Virus Type 1 Infection in a Patient Taking Preexposure Prophylaxis. (29th June 2018) - Colby, Donn J; Kroon, Eugene; Sacdalan, Carlo; Gandhi, Monica; Grant, Robert M; Phanuphak, Praphan; Ananworanich, Jintanat; Robb, Merlin L; Phanuphak, Nittaya
Abstract: We report a case indicating that acquisition of multidrug-resistant human immunodeficiency (HIV) virus type 1 during preexposure prophylaxis with combination tenofovir disoproxil fumarate and emtricitabine or evolution of resistance after HIV seroconversion remains a risk.